Two patients with penile keloids: A review of the literature - (:unkn) unknown (Lippincott Williams and Wilkins, 1997)
Keloid formation on the penis is exceptionally tare even though the penis is frequently subjected to surgical manipulations such as circumcision. Review of the literature revealed a few reports of patients with penile keloids. A 13-year-old Caucasian boy who had a pronounced penile keloid after circumcision and a 56-year-old Caucasian male who had keloid formation on the dorsum of the shaft of the penis after several attacks of penoscrotal hidradenitis suppurativa are presented. They comprise the fifth and the sixth cases of keloid formation in the literature to our knowledge. Intralesional steroid injection and surgical excision are the treatment modalities for this malady. Surgical excision appears to be the choice of treatment for larger lesions that are disabling. Recurrence is still possible, of course.